2019
DOI: 10.1038/s41467-019-08380-1
|View full text |Cite
|
Sign up to set email alerts
|

SMARCA4 loss is synthetic lethal with CDK4/6 inhibition in non-small cell lung cancer

Abstract: Tumor suppressor SMARCA4 (BRG1), a key SWI/SNF chromatin remodeling gene, is frequently inactivated in cancers and is not directly druggable. We recently uncovered that SMARCA4 loss in an ovarian cancer subtype causes cyclin D1 deficiency leading to susceptibility to CDK4/6 inhibition. Here, we show that this vulnerability is conserved in non-small cell lung cancer (NSCLC), where SMARCA4 loss also results in reduced cyclin D1 expression and selective sensitivity to CDK4/6 inhibitors. In addition, SMARCA2, anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
120
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 54 publications
10
120
0
Order By: Relevance
“…Therefore, we do not expect that the 424 downregulation of cyd-1 alone is responsible for the tight cell-cycle arrest. Remarkably, two recent human cancer studies also concluded that SWI/SNF ATPases promote cyclin D1 426 20 expression (Xue et al 2019b(Xue et al , 2019a. This was found to underlie a synthetic lethal interaction between CDK4/6 inhibition and SMARCA4 loss in SCCOHT ovarian carcinoma and non-small 428 cell lung cancers.…”
Section: Acute Swi/snf Depletion Leads To Cell Division Arrest Beforementioning
confidence: 96%
“…Therefore, we do not expect that the 424 downregulation of cyd-1 alone is responsible for the tight cell-cycle arrest. Remarkably, two recent human cancer studies also concluded that SWI/SNF ATPases promote cyclin D1 426 20 expression (Xue et al 2019b(Xue et al , 2019a. This was found to underlie a synthetic lethal interaction between CDK4/6 inhibition and SMARCA4 loss in SCCOHT ovarian carcinoma and non-small 428 cell lung cancers.…”
Section: Acute Swi/snf Depletion Leads To Cell Division Arrest Beforementioning
confidence: 96%
“…The inhibitors of Cdk6 were shown to be a promising agents in the treatment of various tumors via suppressing G1/S phases progression of the cell cycle. Cdk inhibition also upregulated immediate senescence of small cell lung cancer cell, and Cdk4/6 inhibitors were found to be effective on treatment of NSCLC . Therefore, we evaluated the hypothesis that HNF1A‐AS1, together with the downstream regulators miR‐149‐5p/Cdk6, may be involved in the regulation of NSCLC progression.…”
Section: Introductionmentioning
confidence: 99%
“…Cdk inhibition also upregulated immediate senescence of small cell lung cancer cell, 23 and Cdk4/6 inhibitors were found to be effective on treatment of NSCLC. [24][25][26] Therefore, we evaluated the hypothesis that HNF1A-AS1, together with the downstream regulators miR-149-5p/Cdk6, may be involved in the regulation of NSCLC progression.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, TOP2 dysfunction in BAF complex‐deficient tumors, such as ARID1A‐deficient cancers, results in aberrant DNA replication and chromosomal segregation. Based on the abnormality of those cellular functions, BAF complex‐deficient cancer cells are selectively sensitive to inhibitors of the cell cycle regulators cyclin‐dependent kinase (CDK)4/CDK6, the DNA replication checkpoint factor ATR, and the chromosomal segregation factor Aurora kinase A …”
Section: Synthetic Lethal Targets Based On Targeting the Function Of mentioning
confidence: 99%
“…ARID1A mediates the physical interaction between the BAF complex and TOP2. 42 [43][44][45][46][47] The SWI/SNF chromatin remodeling complex is involved in the regulation of several metabolic pathways. The energy supply in cancer cells is derived from ATP generated by the glycolytic pathway.…”
Section: Synthe Ti C Le Thal Targ E Ts Ba S Ed On Targ E Ting the Fmentioning
confidence: 99%